Effects of estradiol and progesterone on secretion of epidermal growth factor and insulin-like growth factor-1 in cultured yak endometrial epithelial cells. (June 2018) - Jiang, J.Y.; Pan, Y.Y.; Cui, Y.; Fan, J.F.; Li, Q.; Yu, S.J.
Highlights: Successful isolation and culture and identificat of yak endometrial epithelial cells. Effects of estradiol and progesterone on secretion of epidermal growth factor and insulin-like growth factor-1 in gene level had been illuminate. Abstract: We isolated and purified yak ( Bos grunniens ) endometrial epithelial cells and assayed different concentrations of estradiol (E2 ) and progesterone (P4 ) with respect to secretion of epidermal growth factor (EGF) and insulin-like growth factor-1 (IGF-1). Uterine epithelia were confirmed with Feulgen staining, karyotype analysis, and immunohistochemistry. Then, cells were treated with E2 and P4 and cultured in serum-free medium for 24 h. EGF and IGF-1 were measured with immunofluorescence, Real-time PCR (RT-PCR), Western blot (WB), and ELISA. When E2 and P4 were applied separately, the expression of EGF and IGF-1 did not change significantly, and EGF and IGF-1 gene and protein expression and epidermal growth factor receptor (EGFR) and insulin-like growth factor receptor (IGFR) gene expression were significantly increased when both hormones were combined. When the hormones were used singly, the optimal concentration of E2 was 10 ng/mL and of P4 was 100 ng/mL. When combined, the optimal E2 concentration was 10 ng/mL and P4 was 10 ng/mL. Thus, E2 and P4 can modulate expression of EGF and IGF-1 in endometrial epithelial cells at the morphological, gene, protein, and exocrine level, which is of great significance to improve the rate of yak embryo implantation and reproduction.